Leptin promotes endothelial dysfunction in chronic kidney disease by modulating the MTA1-mediated WNT/β-catenin pathway - Liu, Bing; Qiao, Jiao; Hu, Jinxiu; Fan, Minghua; Zhao, Yanfang; Su, Hong; Wang, Ziyang; Yu, Qun; Ma, Qiqi; Li, Yanmei; Lv, Zhimei; Wang, Rong (Molecular and cellular biochemistry, 2020)
Endothelial dysfunction (ED) has a high incidence in chronic kidney disease (CKD) and is identified as a precursor to cardiovascular events. Recent studies suggest that leptin may be the missing link between ED and CKD. The objective of this study was to investigate the mechanism by which leptin causes ED and the connection with leptin and indicators of ED in CKD patients. Analysis of leptin-treated human umbilical vein endothelial cells (HUVECs) showed increased expression of interleukin 6 (IL-6), endothelin 1 (ET-1) and human monocyte chemoattractant protein 1 (MCP-1), resulting in F-actin recombination and vinculin aggregation as well as endothelial cell migration. In vitro studies have shown that leptin leads to increased WNT1 expression and the accumulation of β-catenin. Metastasis-associated protein 1 (MTA1), a critical upstream modifier of WNT1 signaling, increased the expression level in leptin-mediated regulation. In contrast, opposite results were observed when cells are transfected with MTA1 or WNT1 shRNA lentivirus vectors. Among 160 patients with CKD and 160 healthy subjects, patients with CKD had significantly higher serum leptin levels than those of the control group, which were positively correlated with increased levels of IL-6, ET-1 and MCP-1. However, these levels were negatively correlated with flow-mediated dilatation (FMD). Hence, these investigations provided novel information on the increased serum leptin levels in CKD patients leading to ED via the MTA1-WNT/β-catenin pathway.